2022
DOI: 10.1038/s41467-022-34754-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and proteomic signatures of type 2 diabetes subtypes in an Arab population

Abstract: Type 2 diabetes (T2D) has a heterogeneous etiology influencing its progression, treatment, and complications. A data driven cluster analysis in European individuals with T2D previously identified four subtypes: severe insulin deficient (SIDD), severe insulin resistant (SIRD), mild obesity-related (MOD), and mild age-related (MARD) diabetes. Here, the clustering approach was applied to individuals with T2D from the Qatar Biobank and validated in an independent set. Cluster-specific signatures of circulating met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 106 publications
3
23
0
Order By: Relevance
“…Hydroxyasparagine, the metabolite with the highest positive weight in our plasma and multi-uid signatures for BMI, is found in the prenatal metabolomic pro les of mothers of obese children 28 . In another study among Arabs, high levels of hydroxyasparagine were found in individuals with mild-obesity-related diabetes 29 . Kynurenine, a metabolite identi ed in our plasma pro le for BMI, is converted from tryptophan in the brain and the periphery and affects various biological actions, including modulating immune response and in ammation 30 .…”
Section: Discussionmentioning
confidence: 90%
“…Hydroxyasparagine, the metabolite with the highest positive weight in our plasma and multi-uid signatures for BMI, is found in the prenatal metabolomic pro les of mothers of obese children 28 . In another study among Arabs, high levels of hydroxyasparagine were found in individuals with mild-obesity-related diabetes 29 . Kynurenine, a metabolite identi ed in our plasma pro le for BMI, is converted from tryptophan in the brain and the periphery and affects various biological actions, including modulating immune response and in ammation 30 .…”
Section: Discussionmentioning
confidence: 90%
“…Of note, N-acetylglucosamine is a recognized contributor to insulin resistance 38 and has been linked with insulin resistance and weight gain in mouse models 38,39 High levels of hydroxyasparagine were reported to play a role in obesity. 25 In addition, both Lachnoclostridium and Acidaminococcus were inversely associated with serum levels of 3 beneficial metabolites: indolepropionate, 3-phenylpropionate, and cinnamoylglycine. The associations between these 2 potentially pathogenic bacteria and T2D could be partially explained by their related microbial metabolites.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, Lachnoclostridium, which was associated with lower fiber intake and higher odds of T2D, showed negative correlations with indolepropionate and 3-phenylpropionate, and was positively linked with several unfavorable metabolites, including N-acetylglucosamine, a metabolite associated with insulin resistance and weight gain, 24 and hydroxyasparagine, a marker of the mild obesity-related diabetes. 25 Because fecal samples were collected after a blood draw, with a median of 10 (interquartile range, 6-14) days, we conducted stratified analyses on the correlations between gut bacteria and serum metabolites by the sample collection time difference (≤10 versus 10-30 days), and correlations between genera and metabolites were highly consistent (Figure S13A and S13B).…”
Section: Integrated Analyses Of Gut Microbiota and Circulating Metabo...mentioning
confidence: 99%
“…More recent evidence suggested that phenylalanine impairs insulin signaling and inhibits glucose uptake through modification of insulin receptor (IR) β [45]. Phenylalanine and 1-carboxyethylphenylalanine were found significantly higher in severe insulin resistant (SIRD) [46].…”
Section: Discussionmentioning
confidence: 99%